Effect of three adjuvants on two fungicides efficiency for Septoria apiicola Speg. control in celery (Apium graveolens L.) - Agámez, Manuel Ricardo; Bejarano, Carlos Andrés; Piedrahita, Wilson de Jesús; Chaves, Bernardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
The late blight of celery disease is caused by the fungus Septoria apiicola; which causes damages on the plant’s foliage affecting its commercial quality up to 70% of its value in absence of control. There are several ways to manage diseases; one is through the use of a chemical control which presents very positive results, however, most of the time this solution is affected by bad practices at application, rain and other adverse conditions raising its cost. In this study were tested the effect and results of two preventive fungicides, copper oxychloride and chlorothalonil, combined with three adjuvants: Mixel® (wetting agent), Figo® (sticker) and Carrier® (carrier). It was used the commercial hybrid of the celery ‘Ferry Ventura’. The study was carried out with two trials during the second semester of 2004 and the first semester of 2005, at Marengo Center located in the municipality of Mosquera, Cundinamarca, in Colombia, (2,556 m above sea level, 645 mm precipitation per year, 14.7ºC annual temperature and 80% relative humidity), using a randomized design of complete blocks with nine treatments and three blocks divided in plots of land of 9.5 m2. The variables measured were: degrees of severity (according to predetermined visual scale), and commercial fresh weight at the time of harvest; additionally an economic analysis was done considering the variable costs, net income and the relation benefit - cost of treatments. In conclusion the best adjuvant for the fungicides was the sticker (Figo) from a biological efficiency point of view; on the other hand and according to the economic evaluation the best treatment was the combination of copper oxychloride with the sticker. The prevented fungicides required adjuvants for best results.